Thorax Virtual Anatomy Lab for Preprofessional Health Sciences Students - Penprapa Klinkhachorn; Barbara Kraszpulska; Edwin Allen; Jeffrey Altemus; Elizabeth Walker (Association of American Medical Colleges, 2009)
Abstract Introduction This module was developed at the West Virginia University (WVU) Robert C. Byrd Health Science Center. This health center serves as part of the West Virginia University educational support programs pipeline. The objective of this pipeline is to increase the number of college-bound students among underrepresented secondary students and help meet West Virginia's need for health care providers. This is particularly important in the more remote and economically disadvantaged areas of the second most rural state in America. This program was developed because the mountainous terrain, lack of roads, and the location of medical centers in rural cities conspires to promote poor access to health care and education across most of the state. This educational pipeline draws students from the entire state, building a rural health care network across the state that incorporates rural health care into the curriculum. Methods This online tutorial serves as an introduction to human thorax gross anatomy for pre-professional health sciences students. Its objective is to stimulate active self-directed learning by integrating gross anatomy into a structured format that is readily accessible for local and distance learning. The thorax and its parts are dissected, photographed, and the images are digitized for computer-assisted instruction. They are constructed with Flash software for interactive learning. This knowledge is critical to prepare students for their clinical years. Results We have successfully trained health-sciences students to work in rural community-based settings. The university's extended learning departments have encouraged faculty to reach out to distance learners everywhere to provide more learning possibilities. The human anatomy course for which this resource was created was offered beginning in 2002. The course has been well received by non-traditional students and WVU students taking the course during the summer session at home. Out-of-state and international students needing a general anatomy prerequisite for more advanced study also take this course. The program serves nursing, dental hygiene, pharmacy, pre-medical and pre-dental students, physical and occupational therapy, athletic trainers, radiology technicians, speech therapy, and emergency medicine technicians. Discussion This tutorial addressed the need for an online anatomy lab class to teach learners a large volume of information without overwhelming them. Active learning was achieved by grouping the contents into parts dealing with the thorax anatomy (e.g., the wall, lungs, heart, and mediastinum). The use of drag-and-drop labels on high-quality images provides interactive learning experiences. It challenges students with identification and matching exercises, as well as cadaver lab quizzes. Preprofessional students study the materials in the library, at home, or in the dissection laboratory and other study areas. Virtual and real visits to the anatomy lab typically accompany these online assignments. The combination of this virtual lab and general anatomy course provide sufficient information for students to fulfill prerequisite requirements and to prepare them for professional level anatomy courses, (i.e., medical, dental, and graduate courses in anatomy).